EXPLORING THE ETHICAL CRISIS OF THE TEACHING PROFESSION: REFLECTIONS ON CASES OF TEACHER VIOLENCE AGAINST STUDENTS - Yesi Airohmah; Febilia Jati Witari; Aang Kunaepi (JGK (Jurnal Guru Kita), 2023)
This study aims to analyze the teacher ethical crisis based on cases of violence against students in 2023. Using qualitative methods and a library research approach, data was obtained from various sources such as books, journals, online newspapers and previous research. The results show that 1) the teacher ethical crisis is seen in the aspect of implementing morals, with violations such as lack of patience and compassion, 2) factors of violence in schools include teachers' lack of understanding of the consequences of violent acts, authoritarian teaching patterns, and the use of violence as a method of discipline 3) Violence prevention requires holistic solutions such as aqidah development, value instillation, anti-violence socialization, psychological support, classroom management training, human rights education, and professional ethics.